2005
DOI: 10.1001/archderm.141.3.373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV Photographs, Photoaging Information, and Use of Sunless Tanning Lotion on Sun Protection Behaviors

Abstract: Objectives: To examine the efficacy of UV photographs and information about photoaging (eg, wrinkles and age spots) for increasing the sun protection intentions and behaviors of young adults and to determine whether any effects of this appearancebased intervention could be enhanced by providing a non-UV alternative for achieving a tan (ie, sunless tanning lotion).Design: Randomized control trial with 1-month followup.Setting: Two universities in Southern California.Participants: A volunteer sample of 146 colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(79 citation statements)
references
References 42 publications
5
73
1
Order By: Relevance
“…Several individuals have remarked that tans achieved through sunless tanning products do not look natural (Mahler et al, 2005). Oftentimes these products turn the skin orange, leaving a "streaked" appearance.…”
Section: Perceived Risk and Sunless Tanning Product Usementioning
confidence: 99%
See 1 more Smart Citation
“…Several individuals have remarked that tans achieved through sunless tanning products do not look natural (Mahler et al, 2005). Oftentimes these products turn the skin orange, leaving a "streaked" appearance.…”
Section: Perceived Risk and Sunless Tanning Product Usementioning
confidence: 99%
“…For the past several decades, researchers across disciplines have sought to understand the mechanisms underlying sun exposure and sun-protection behaviors (Mahler et al, 2005). However, little is known about tanning product consumption in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…18,[20][21] Indeed, a number of studies, predominantly by Mahler et al, have demonstrated that UV photoaged photographs are effective in promoting skinprotective practices. 5,[22][23][24][25][26][27] Such studies suggest that appearance-based UV photoaged photographic interventions have the potential to motivate the kinds of skin-protective practices that ultimately will produce the desired health benefit of a reduction in skin cancer rates.…”
Section: Uv Photoaged Photographymentioning
confidence: 99%
“…While researchers have predominantly used quantitative experimental methodologies (e.g., randomised 22,24,26 /nonrandomised 23,27 control designs and self-report measures) to evaluate sun-tanning intentions and skin-protective behaviours of participants' post viewing their UV photoaged image, no studies (as far as the authors are aware) have explored the impact of UV photoaged photography on behaviour from a qualitative perspective. Hence, it is posited that this qualitative study will enrich the existing quantitative findings by focusing explicitly on people's perception of self within their social context.…”
Section: Uv Photoaged Photographymentioning
confidence: 99%
“…For example, Gibbons and Mahler et al describe a reduction in college students' intention to tan, tanning behavior, and measured skin tan (using a calorimeter) when UV photography was employed. [8,13,16] Most other research has identified that highlighting the connection between UV exposure and its effect on photoaging has given other (often younger) populations another reason to protect themselves from the sun. [10-14, 16, 17] Taken as a whole, these findings suggest that a personalized, interactive approach, with emphasis on high-risk populations, may be an efficacious and valuable approach to skin cancer prevention and awareness in high risk groups.…”
Section: Introductionmentioning
confidence: 99%